3D Imaging Technologies in Atherosclerosis - Trivedi, Rikin; Saba, Luca; Suri, Jasjit S. (Springer US : Imprint: Springer, 2015)
This book covers the latest developments in imaging of atherosclerosis. Topics covered include multi-detector-row technology and the use of dual energy and multi-spectral imaging. Magnetic Resonance (MR) imaging of carotid arteries, intra-cranial vessels, and coronary arteries are also discussed in detail. Special attention is given to Computer Tomography (CT) imaging of intra-cranial vessels, coronary arteries, and atherosclerosis in the lower limb. This is an ideal book for graduate students and researchers in the field of medical imaging, especially of atherosclerosis. This book also: ·Covers state-of-the-art imaging of atherosclerosis ·Enables the reader to understand the advantages of each modality in visualizing atherosclerosis ·Describes the advances of various technologies, including dual energy and multi-spectral imaging.